1995
DOI: 10.1055/s-2007-1013803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Early Results of Coronary Artery Bypass Grafting With and Without Extracorporeal Circulation

Abstract: To compare the safety and efficacy of coronary artery bypass grafting without using extracorporeal circulation with standard cardiopulmonary bypass technique, based on certain early postoperative criteria, we designed a fully randomized and prospective study on two similar groups of 25 patients (off-pump and on-pump groups). The groups were compared for hemodynamic data (cardiac index, systemic vascular resistance, left- and right-ventricular stroke-work indices, inotropic and mechanical support needs) and enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 2 publications
0
22
0
5
Order By: Relevance
“…A total of 6256 potentially relevant citations were identified and screened, of which 5232 originated from MEDLINE; 224 articles were retrieved for detailed evaluation, of which 22 fulfilled eligibility criteria ( Figure 1) (25)(26)(27)(28)(29)(30)(32)(33)(34)(35)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 6256 potentially relevant citations were identified and screened, of which 5232 originated from MEDLINE; 224 articles were retrieved for detailed evaluation, of which 22 fulfilled eligibility criteria ( Figure 1) (25)(26)(27)(28)(29)(30)(32)(33)(34)(35)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All 22 studies reported on the incidence of AKI, with seven studies defining AKI exclusively as the need for dialysis (25,26,33,47,49 -51). Six studies did not describe the criteria used to define AKI (27,34,35,42,46,48). The remaining nine studies defined AKI using variable absolute or relative increases in serum creatinine, decreases in GFR, decreases in urine output, or need for dialysis (Table 2) (28 -30,32,43-45, 52,53).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…La revascularización de la arteria descendente anterior se ha efectuado clásicamente con el uso de circulación extracorpórea y realizando una anastomosis entre la arteria mamaria interna izquierda y la arteria descendente anterior [1][2][3][4][5][6][7][8][9][10][11][12][13][14] .…”
Section: Discussionunclassified
“…Algunos estudios han demostrado buenos resultados con una baja morbilidad y mortalidad en el período post operatorio, menores costos y uso de hemoderivados [7][8][9][10][11] .…”
Section: Introductionunclassified